Strategi Penyelesaian Konflik dalam Novel Pulang Karya Leila S Chudori Kajian Sosiologi Sastra: Conflict Resolution Strategies in the Novel Pulang by Leila S. Chudori: A Sociology of Literature Study - Br Munthe, Indriyani Rehulina; Dardanila, Dardanila; Marsella, Emma (Transformatika: Jurnal Bahasa, Sastra, dan Pengajarannya, 2025)
This study aims to describe the conflict resolution strategy in Pulang by Leila S Chudori. This study uses a qualitative approach with a descriptive method. This type of research uses a qualitative research method with a descriptive method, where collecting and analyzing scientific data then describing the facts in detail intends to find out the conflict resolution strategy in the novel Pulang by Leila S Chudori. To deal with this situation, individuals often use various conflict resolution strategies that reflect their personality, values, and social context. In the novel Pulang by Leila S. Chudori, there is a description of how the characters deal with various types of conflicts, both personal, social, and political. The research studied is the conflict resolution strategy used by characters in literary works. This approach provides an overview of the conflict resolution strategy used by characters in the novel Pulang with Pruitt and Rubin's theory, namely: (a) Contending (Contending) using authority or pressure to win a conflict or debate, resolving the conflict according to their wishes without regard to the interests of the other party. (b) Yielding (Giving in) Hananto's character lowers his aspirations or desires (to perhaps go out of town or abroad) in order to maintain harmonious relations and avoid further conflict with Surti., (c) Problem solving (Problem Solving) The parties who use this strategy maintain their own aspirations, but simultaneously seek ways to reconcile with the interests of the other party. Agreements in problem solving can be in the form of compromises, (d) Withdrawing (Withdrawing) the withdrawing strategy is implemented by leaving an increasingly heated debate, in the hope of avoiding emotional harm and keeping the situation from getting worse., and (e) Inaction (Silence) This strategy is temporary and can provide time for the parties involved to reflect or observe the development of the situation before making further decisions.